PEDAGOGICAL ANALYSIS OF THE DEVELOPMENT, HISTORICAL PROGRESS, AND REFLECTION OF NATIONAL VALUES OF PHYSICAL EDUCATION AND ECOLOGICAL CULTURE - K.B. Muhammadiev (Galaxy International Interdisciplinary Research Journal, 2022)
Nature is a place for living beings to live, a source of precious blessings, and it is the duty of every person to protect it. In this regard, our nation has its own rich national-historical traditions.